Validation of Photographic Food Atlas. - Fry, Helen. (Tufts University. Tisch Library., 2016)
This detailed presentation presents the effort surrounding the creation of a photographic food atlas. Design, reasoning, methods, and results are shared. Delivered on Day 2 of the 2014 Scientific Symposium.; Nutrition School: NIL Symposium Presentations, 2014.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy